2019
DOI: 10.1097/aog.0000000000003062
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects and Long-Term Cost-Effectiveness of Universal Hepatitis C Testing in Prenatal Care

Abstract: Objective-To estimate the clinical effects and cost-effectiveness of universal prenatal hepatitis C screening, and to calculate potential life expectancy, quality of life, and health care costs associated with universal prenatal hepatitis C screening and linkage to treatment. Methods-Using a stochastic individual-level microsimulation model, we simulated the lifetimes of 250 million pregnant women matched at baseline with the U.S. childbearing population on age, injection drug use behaviors, and hepatitis C vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Models have shown that universal prenatal HCV screening improves health outcomes in women with HCV infection, improves identification of HCV in at-risk neonates, and is costeffective. 263 Screening remained cost-effective at a prevalence of 0.07%, which is translatable to a European population. 264 Universal HCV testing in pregnant women is therefore recommended as part of the strategy for global elimination.…”
Section: Treatment Of Chronic Hepatitis C In Pregnant Womenmentioning
confidence: 99%
“…Models have shown that universal prenatal HCV screening improves health outcomes in women with HCV infection, improves identification of HCV in at-risk neonates, and is costeffective. 263 Screening remained cost-effective at a prevalence of 0.07%, which is translatable to a European population. 264 Universal HCV testing in pregnant women is therefore recommended as part of the strategy for global elimination.…”
Section: Treatment Of Chronic Hepatitis C In Pregnant Womenmentioning
confidence: 99%
“…56 Moreover, recent models of Pharmacoeconomics suggest that the adoption of universal screening for HCV in prenatal care would have undoubted advantages on the outcome of mother, newborn and is a cost-effective practice. 57 In women of childbearing age who are infected with HCV, antiviral treatment prior to pregnancy can improve maternal health and eliminate the risk of MTCT. Prevention of MTCT is limited by the absence of universal guidelines for HCV screening during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Although real-world data informing screening during each pregnancy are lacking, a modeled analysis suggests that hepatitis C screening during each pregnancy would be costeffective. Using a hepatitis C prevalence of 0.38% among pregnant women, as determined from national birth certificate data, the analysis found that universal hepatitis C screening during the first trimester of each pregnancy under a health care perspective compared with the current practice of risk-based screening had an ICER of $41,000/QALY gained (93). The model assumed no hepatitis C treatment would be offered until after 6 months postpartum and that 25% of women would be linked to care, with 92% of those linked initiating treatment.…”
Section: Cost-effectiveness Considerationsmentioning
confidence: 99%